A Psycholinguistic Analysis of Inter-Ethnic Views of Ethics - Taraban, Roman; Saraff, Sweta; Zasiekin, Serhii; Biswal, Ramakrishna (East European Journal of Psycholinguistics, 2022)
In this paper we describe a collaborative, cross-cultural project whose focus is on developing an interactive pedagogy for undergraduate students that delivers a culturally relevant ethical activity, using an internet platform to widen the scope of learning at an international level. The ongoing collaborative project described here is implemented through a website, the Ethical Engineer (https://ethicalengineer.ttu.edu), that provides an open and unique online digital platform for developing a community of students committed to the discussion of ethics from a global perspective. A goal of this project was to gain insights into similarities and differences between Indian, Ukrainian, and USA respondents in their reasoning about a hypothetical ethical dilemma. Two complementary methods of analysis were applied to students’ responses. First, a well-known method for text analysis, Linguistic Inquiry and Word Count (LIWC2022) was used to identify topics and perspectives in students’ essays that distinguished the three groups. These analyses were followed by naïve Bayesian analyses that were used to further identify characteristic conceptual differences between the three ethnic groups. We discuss how the Ethical Engineer platform could be further developed by providing students with immediate substantive feedback to their written responses, in order to extend the learning benefits to students from participation on the website. The analytic methods described here demonstrate ways to gain knowledge of globally-diverse students’ thinking.